PERFORMANCE AND EXHAUST GAS TEMPERATURE INVESTIGATION OF CERAMIC, METALLIC AND FeCrAl CATALYTIC CONVERTER IN GASOLINE ENGINE - Hadi Pranoto; Dafit Feriyanto; Supaat Zakaria (Universitas Mercu Buana, 2019)
Catalytic converter (CATCO) and its effect on engine performance and exhaust gas temperature became an exciting field in automotive research. In this study purposed to compare existing CATCO which is ceramic and metallic with FeCrAl CATCO that treated with a combination of ultrasonic bath and electroplating technique in 30 minutes holding time (UB+EL 30 min). This study proposed to select an appropriate CATCO that used in a gasoline engine to increase the performance and to reduce the exhaust gas temperature as well as its potential to reduce the exhaust gas emission. Mitsubishi 4G93 conducted this analysis with 1.8 L and 10.5 compression ratio with a variable speed of 100, 2000 and 3000 rpm and different engine load of 10, 20 and 30%. The result shows that the FeCrAl CATCO was more useful to reduce fuel consumption up to 66.42% and increase torque up to 15.79% as well as reduce exhaust gas temperature up to 30.11% as compared to ceramic and metallic CATCO. It can be concluded that FeCrAl CATCO coated by UB+EL 30 min was recommended to increase engine performance and to reduce exhaust gas emission.